THE EFFECT OF RELIGIOSITY ON LIFE SATISFACTION WITH ALTRUISM AS A MEDIATING VARIABLE - Taimoor Ahmed Shaikh; M. Parnawa Putranta; J. Ellyawati (Universitas 17 Agustus 1945 Semarang, 2023)
Background: A nurse who has strong religiosity has close relationship to God, doing the best at the job as the part of altruism behavior, and it will increase the life satisfaction. Aim: This article therefore aims at analyzing the influence of religiosity on life satisfaction with altruism as mediation variable Setting: Siloam Hospital and PKU Muhammadiyah Hospital Yogyakarta. Methods: A cross-sectional design was employed and 187 respondents were selected Siloam Hospital and PKU Muhammadiyah Hospital Yogyakarta. Quantitative data were collected and analyzed by using descriptive and inferential statistics in which frequencies, percentages, mean, standard deviation and regression, also Sobel test were employed. Results: The results show that religiosity has positive effect on altruism, religiosity has positive effect on life satisfaction, and this study also has result that altruism mediating the effect of religiosity on life satisfaction. Conclusion: Altruism inherent in all religions is a determinant of life satisfaction. Individuals who have good religiosity will be encouraged to always do good on the basis of religion and it increases the individual's life satisfaction.